2000
DOI: 10.1146/annurev.astro.38.1.379
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Burst Afterglows

Abstract: The discovery of counterparts in X-ray and optical to radio wavelengths has revolutionized the study of γ -ray bursts, until recently the most enigmatic of astrophysical phenomena. We now know that γ -ray bursts are the biggest explosions in nature, caused by the ejection of ultrarelativistic matter from a powerful energy source and its subsequent collision with its environment. We have just begun to uncover a connection between supernovae and γ -ray bursts, and are finally constraining the properties of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
250
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(260 citation statements)
references
References 192 publications
(172 reference statements)
8
250
1
1
Order By: Relevance
“…The parameter m(t) in Equation 4 has a magnitude dependent on the total number of fissions and a known time dependence. The expected GRB afterglow energy distribution is approximated by  ≈ -1 (Paradijs et al 2000) which again is in very nice agreement with the spectral shape of the delayed gamma photon distribution of a fission criticality event given in Equation (4).…”
Section: Grb Energy Spectrasupporting
confidence: 80%
“…The parameter m(t) in Equation 4 has a magnitude dependent on the total number of fissions and a known time dependence. The expected GRB afterglow energy distribution is approximated by  ≈ -1 (Paradijs et al 2000) which again is in very nice agreement with the spectral shape of the delayed gamma photon distribution of a fission criticality event given in Equation (4).…”
Section: Grb Energy Spectrasupporting
confidence: 80%
“…Since then, several X-ray, optical, and radio counterparts of GRBs have been detected. These multiwavelength afterglow observations can be explained reasonably well by simple Ðreball models (for recent reviews see Piran 1999 ;van Paradijs, Kouveliotou, & Wijers 2000). GRB distance determinations are crucial in the e †ort to establish the physical nature of their progenitor(s).…”
Section: Introductionmentioning
confidence: 68%
“…Studies of afterglows confirmed the synchrotron shock model (e.g., Wijers, Rees, & Mészáros 1997), and their physics now seems to be reasonably well understood (see, e.g., Mész-áros 2002, Waxman 2003, andreferences therein). Other recent reviews include Kulkarni et al (2000), van Paradijs, Kouveliotou, & Wijers (2000), Hurley, Sari, & Djorgovski (2003), and Djorgovski et al (2002Djorgovski et al ( , 2003.…”
Section: Introductionmentioning
confidence: 99%